2015
DOI: 10.1007/s13280-015-0717-x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological abnormalities in gonads of the Baltic herring (Clupea harengus membras): Description of types and prevalence in the northern Baltic Sea

Abstract: Due to heavy anthropogenic influence and variation of the environmental conditions in the Baltic Sea, reproductive disorders are becoming a major environmental concern. We show here an increasing prevalence of gonadal malformations in the Baltic herring (Clupea harengus membras), a key species of the Baltic ecosystem and important in commercial fishery. During 1987-2014, the spawning herring population in the Archipelago Sea (AS) (North Baltic Sea, Finland) was monitored annually and analyzed for gross morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Due to its vulnerability to external perturbations reproduction is a sensitive environmental indicator (Rajasilta et al 2016). Many types of gonads malformations such as hermaphroditism, atrophy, compartmentations, and asymmetry have been described for a number of fish populations in both sexes (Bernet et al 2004;Hliwa et al 2011;Sopinka et al 2012;Rajasilta et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Due to its vulnerability to external perturbations reproduction is a sensitive environmental indicator (Rajasilta et al 2016). Many types of gonads malformations such as hermaphroditism, atrophy, compartmentations, and asymmetry have been described for a number of fish populations in both sexes (Bernet et al 2004;Hliwa et al 2011;Sopinka et al 2012;Rajasilta et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Due to its vulnerability to external perturbations reproduction is a sensitive environmental indicator (Rajasilta et al 2016). Many types of gonads malformations such as hermaphroditism, atrophy, compartmentations, and asymmetry have been described for a number of fish populations in both sexes (Bernet et al 2004;Hliwa et al 2011;Sopinka et al 2012;Rajasilta et al 2016). Rajasilta et al (2016) have reported that asymmetry was the most frequent gonad type that deviated from normal in the Archipelago Sea, which was observed during the entire study period at varying but low frequencies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Morphological abnormalities of the gonads is a phenomenon that has been reported from numerous wild fish populations [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. These morphological alterations are of concern as they may be indicative of a disease and/or may impair the reproductive success of the populations [11,15,16].…”
Section: Introductionmentioning
confidence: 99%